2001
DOI: 10.1183/09031936.01.17508380
|View full text |Cite
|
Sign up to set email alerts
|

Sleep and daytime sleepiness in upper airway resistance syndrome compared to obstructive sleep apnoea syndrome

Abstract: Sleep and daytime sleepiness in upper airway resistance syndrome compared to obstructive sleep apnoea syndrome. C. Guilleminault, Y. Do Kim, S. Chowdhuri, M. Horita, M. Ohayon, C. Kushida. #ERS Journals Ltd 2001. ABSTRACT: This study has investigated differences in the nocturnal sleep and daytime sleepiness among patients with obstructive sleep apnoea syndrome (OSAS), upper airway resistance (UARS), sleep hypopnoea syndrome, and normal control subjects, using sleep scoring and spectral activity analysis of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
62
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(67 citation statements)
references
References 25 publications
5
62
0
Order By: Relevance
“…The development of slow wave sleep is also abnormal, with persistence of a large number of "power delta" at the end of sleep cycles. Both abnormalities may explain the symptoms of daytime sleepiness, insomnia and fatigue in patients with UARS (Guilleminault 2001a). Black et als found that visually undetectable EEG alterations may occur during breathing disturbances in the absence of arousal (Black 2000).…”
Section: Diagnosismentioning
confidence: 99%
See 2 more Smart Citations
“…The development of slow wave sleep is also abnormal, with persistence of a large number of "power delta" at the end of sleep cycles. Both abnormalities may explain the symptoms of daytime sleepiness, insomnia and fatigue in patients with UARS (Guilleminault 2001a). Black et als found that visually undetectable EEG alterations may occur during breathing disturbances in the absence of arousal (Black 2000).…”
Section: Diagnosismentioning
confidence: 99%
“…Hypersomnolence is the principal daytime manifestation of sleep disordered breathing. Excessive sleepiness resulting from increased breathing effort and sleep disruption is the guide symptom of UARS patients (Guilleminault 1993(Guilleminault , 2001a. Drowsiness related to general exhaustion has a negative impact on quality of life.…”
Section: Symptomsmentioning
confidence: 99%
See 1 more Smart Citation
“…The paper by Guilleminault et al [10] requires some comments. They recruited 12 patients with UARS who are described as representative of the general UARS patient.…”
mentioning
confidence: 99%
“…In this issue of the European Respiratory Journal, Guilleminault et al [10] present data on spectral analysis of sleep and sleep architecture in matched groups of normal subjects and patients with UARS, sleep apnoea syndrome (SAS) and sleep hypopnoea syndrome (SHS). They contend that according to the data, SAHS and UARS patients have different brain activity during sleep and cannot therefore be considered as similar.…”
mentioning
confidence: 99%